Kejadian Diare Balita di Kecamatan Kotagede Yogyakarta: Space-Time Permutation Model - Dian Maya Sari; Sulistyawati Sulistyawati; Nurma Aqmarina (Universitas Faletehan, 2024)
There were 99,338 cases of diarrhea detected in Special Region of Yogyakarta (DIY) with just 8,442 treated. This study aimed to determine the relationship between the incidence of diarrhea in toddlers and the place and time in Kotagede District, DIY. This quantitative study employed a space-time permutation model method. The population of this study were toddlers registered to visit Public Health centers in Kotagede Regency, namely the working area of Kotagede I Health Center and Kotagede II Health Center as many as 200 cases. Meanwhile, this study employed a sample size of 155 chosen based on inclusion and exclusion criteria. The outcomes of the analysis were univariate. The gender characteristic that caused the most diarrhea were males (53%), the characteristic of the age was one year ≤ 2 years (31%), most of the parents' education was high school graduates (42.6%), the most occupational characteristic of parents was laborers (33.5%), and the highest cases occured in Prenggan (38.1%). SaTScan statistical results showed that there was an aggregation of time for one month; the first significant cluster was Purbayan (p-value 0.0068) with a cluster radius of 0.28 km; the second significant cluster was Prenggan (p-value 0.021) with a cluster radius of 0.13 km; The first significant seven-day cluster time aggregation was Purbayan (p-value 0.010) with a cluster radius of 0.28 km; the second significant cluster was Rejowinangun (p-value 0.031) with a cluster radius of 0.16 km; and the third significant cluster was Prenggan (p-Value 0.038) with a cluster radius of 0.13 km. There was a spatio-temporal relationship between place and time with the incidence of diarrhea among toddlers in Kotagede Yogyakarta.